Methodology for calculating the consequences of breakthroughs (destruction) of hydraulic structures of critical infrastructure - Kotsyuruba, Volodymir; ProshchynІhor (Social Development and Security, 2024)
Purpose: to improve the method of forecasting the consequences of emergency situations at hydrotechnical structures of a terrorist nature. Method: the main methods of research are methods of: analysis and synthesis Theoretical implications:8 dangerous factors that arise as a result of the destruction (damage) of hydraulic units and can cause losses and affect the performance of a combat mission have been identified. Practical implications: The proposed technique is of significant importance for the theory of civil protection and can be used not only for calculations when forecasting the scale and volume of the negative impact of the consequences of the destruction of hydrotechnical structures, but also for conducting further scientific research. Value: the developed method takes into account the decrease in the patency of the area, the heterogeneity of the density of the built-up area in the urbanized area and the population density of the emergency situations within the flood zones Papertype: practical.